2016
DOI: 10.18632/oncotarget.13815
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of progression-free survival of first-line tyrosine kinase inhibitors in patients with non-small cell lung cancer harboring leu858Arg or exon 19 deletions

Abstract: BackgroundGefitinib, erlotinib and afatinib provide remarkable response rates and progression-free survival compared to platinum-based chemotherapy in patients with non-small cell lung cancer harboring epidermal growth factor receptor-activating mutations, and are therefore standard first-line treatment in these patients. However, no study has compared these drugs regarding progression-free survival.Materials and MethodsWe conducted this retrospective study at a single medical center in Taiwan from February 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 49 publications
4
57
0
Order By: Relevance
“…Compared with erlotinib, afatinib appeared to have similar efficacy in terms of progression‐free survival as first‐line treatment of EGFR mutant patients, but was associated with longer progression‐free survival (2.6 vs . 1.9 months, HR 0.81, 95% CI, 0.69 to 0.96) and overall survival (7.9 vs .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with erlotinib, afatinib appeared to have similar efficacy in terms of progression‐free survival as first‐line treatment of EGFR mutant patients, but was associated with longer progression‐free survival (2.6 vs . 1.9 months, HR 0.81, 95% CI, 0.69 to 0.96) and overall survival (7.9 vs .…”
Section: Resultsmentioning
confidence: 99%
“…The effects of afatinib were investigated in four studies, including two observational ones directly comparing the three agents on progression-free survival 89 or selected adverse events, 98 one randomized trial comparing afatinib with gefitinib on all efficacy and safety outcomes, 97 and one randomized trial comparing afatinib with erlotinib on all efficacy and safety outcomes. 103 Compared with gefitinib, afatinib appeared to be associated with longer progression-free survival as first-line treatment of EGFR mutant patients, 89,97 but the benefit was considerably different between studies (>18 versus 11.4 months in the observational one; 11.0 versus 10.9 months in the randomized trial), and there was no evidence that afatinib prolonged overall survival.…”
Section: Comparison Of Afatinib With Gefitinib and Erlotinibmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a recent study analyzing the BM subgroups of the LUX-Lung 3 and LUX-Lung 6 trials revealed a significant improvement in PFS for the afatinib group compared with the chemotherapy group. 4 Although the effects of afatinib have been compared with those of other EGFR-TKIs, including one observational study that compared three agents in terms of PFS 19 and one randomized trial that compared afatinib with gefitinib, 20 there has been no previous study comparing three TKIs in terms of the prevention and treatment of BM. In our study, the median PFS (8.2 months) of the BM patients who received afatinib was similar to that (8.2 months) reported for the results of the LUX-Lung 3 and LUX-Lung 6 trials, 6 and to that reported for real-world practice (9.2 months).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the NSCLC patients with different EGFR gene mutations undergo different responses to first-, second-, and third-generation EGFR-TKIs. These patients also display different progression-free survival (PFS) and OS [19][20][21][22][23]. NSCLC patients harboring deletions in exon 19 respond better to EGFR-TKIs with longer PFS and OS compared with other mutations [19,20].…”
Section: Discussionmentioning
confidence: 99%